Nebrija and his time: the building of a language - Monreal Pérez, Juan Luis (Revista de Filología Románica, 2012)
Nebrija paints a relevant figure for us today because he was a great humanist, for the part he played in vernacular languages, and, particularly, because of his ‘Grammar of the Castilian Language’. He was the first philologist who dedicated himself to the study of a romance language: the Castilian Spanish. His wealth of philological knowledge was put to use against a tradition that deemed only the classical and noble languages of Greek and Latin as worthy of study. His work as a philologist and man of letters bears significance and has been recognised by everyone throughout history. This is especially due to his prolific scientific output.